Dental appointment no-shows: why do some parents fail to take their children to the dentist? - ULRIKA HALLBERG, ELISABETH CAMLING, INGEGERD ZICKERT, AGNETA ROBERTSON, & ULF BERGGREN (IAPD and Blackwell, 2008)
Caries is the single most common disease in childhood 1–4 . If caries develops early in life it is more likely that the individual will develop caries in the permanent teeth later in life 5 . Hence, caries has a lifelong impact on children’s oral health status. Caries can also affect a child’s growth in terms of lower weight and height due to difficulties in eating 5 . Many children living in multicultural, low socioeconomic areas of Sweden show poor oral health. Several studies have demonstrated that immigrant children and children in socially deprived communities have significantly more caries than the average child 7–9 . Children from low-income families also have lower compliance with treatment 10 .